Investigating Host Microbiota Relationships Through Functional Metagenomics - Laville, Elisabeth; Perrier, Josette; Bejar, Nada; Maresca, Marc; Esque, Jeremy; Tauzin, Alexandra S.; Bouhajja, Emna; Leclerc, Marion; Drula, Elodie; Henrissat, Bernard; Berdah, Stephane; Di Pasquale, Eric; et al. (Frontiers in Microbiology, 2019)
The human Intestinal mucus is formed by glycoproteins, the O- and N-linked glycans which constitute a crucial source of carbon for commensal gut bacteria, especially when deprived of dietary glycans of plant origin. In recent years, a dozen carbohydrate-active enzymes from cultivated mucin degraders have been characterized. But yet, considering the fact that uncultured species predominate in the human gut microbiota, these biochemical data are far from exhaustive. In this study, we used functional metagenomics to identify new metabolic pathways in uncultured bacteria involved in harvesting mucin glycans. First, we performed a high-throughput screening of a fosmid metagenomic library constructed from the ileum mucosa microbiota using chromogenic substrates. The screening resulted in the isolation of 124 clones producing activities crucial in the degradation of human O- and N-glycans, namely sialidases, β-D-N-acetyl-glucosaminidases, β-D-N-acetyl-galactosaminidases, and/or β-D-mannosidases. Thirteen 13 of these clones were selected based on their diversified functional profiles and were further analysed on a secondary screening. This step consisted of lectin binding assays to demonstrate the ability of the clones to degrade human intestinal mucus. In total, the structural modification of several mucin motifs, sialylated mucin ones in particular, was evidenced for nine clones. Sequencing their metagenomic loci highlighted complex catabolic pathways involving the complementary functions of glycan sensing, transport, hydrolysis, deacetylation and deamination, which were sometimes associated with amino acid metabolization machinery. These loci are assigned to several Bacteroides and Feacalibacterium species highly prevalent and abundant in the gut microbiome and explain the metabolic flexibility of gut bacteria feeding both on dietary and human glycans.